(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Zomato is green banking, which may have framed 10% Zomato credit for every Rs. 300 spent on the app, encouraging customers on eco-friendly orders. Using significant features such as electronic banking services, paperless transactions and green loans, in addition to manufacturer social obligation systems, this examine analyzes the consequences of inexperienced banking practices with the help of the customer satisfaction approach. The mixed-methods approach to collecting research data involved primary data obtained from basic surveys of bank customers and secondary data obtained from financial reports and industry case studies. The results indicated greater customer satisfaction among banks who engaged in eco-friendly initiatives, with sustainability measures showing positive signs of influencing customer patronage. The study implication implies the adoption of this green banking strategy will help financial institutions to widen their engagement with customers and competitive advantage in the upcoming marketplace. The study also provides some suggestions for how the banks can strike a more equitable approach between sustainability activity and customer experience.